Synthesis and Application of 2:1 Zinc Complex Dyes and Their Antibacterial Properties - TELI, M.D.; SEKAR, N.; JAIN, A.; PRABHU, K.H. (Asian Journal of Chemistry, 2010)
2:1 Zinc complex monoazo acid dyes have been prepared. Six commercially available Omega Chrome dyes and other three dyes based on 1-amino-2-naphthol-6-sulphonic acid and the couplers 1-naphthol-4-sulphonic acid, 2-naphthol and 2-naphthol-6-sulphonic acid were used in preparing the complexes. All these dyes were analyzed using atomic absorption spectra and thin layer chromotogrphy. The dyeing of wool fabric was carried with these dyes and their antibacterial activity of dyed fabric was assessed. Dyeings using zinc complexed dyes showed prominent antibacterial activity. The performance properties such as wash fastness, fastness to dry cleaning and light fastness were also measured. Intense colour value was obtained for all the dyes synthesized. Very good fastness to washing and dry cleaning has also been observed, where as light fastness of the deyings was of moderate to good degree.